Identifikasi Jamur Candida Sp Pada Kuku Jari Tangan Dan Kuku Kaki Petani Dusun Panaikang Desa Bontolohe Kecamatan Rilau Ale Kabupaten Bulukumba - Khusnul Khatimah; Idris Mone; Nurwahidah Fa’al Santri (Jurnal Media Laboran, 2018)
Candidiasis or candidosis is a fungal infection that causes abnormalities in the nail caused by candida. This disorder can arise due to poor hygiene in the nail area, especially at the tip of the nail. In addition to nails, candida can also attack the mouth, vaginal skin and lungs. This study aims to determine the percentage of farmers infected with candida and to find out the dominant types of fungi that infect the nails of these farmers. The sample used in this study was nail scrapings from 10 farmers and then microscopically and culturally examined. The results of the study showed that there were 5 samples of nail scraping spores which were found while Hifa examination was not found in the nail scrapings, while for culture tests there were 4 farmers whose nails were infected with onychomycosis with Candida fungi, Aspergillus fungi. Of the 5 infected farmers, 4 people had nail disorders and 6 without nail abnormalities. Conclusion: Based on the results of the study showed that 10% of farmers were infected with 30% of oncomycosis with Candida and Aspergillus sp.